Dental agenesis: review of the literature and report of two cases - Arboleda-A., Luz Ángela; Echeverri-E., Jacqueline; Restrepo-P., Luz Ángela; Marín-B., Martha Lucía; Vásquez-P., Gonzalo; Gómez-M., July Catalina; Manco-G., Hugo Alexánder; Pérez-S., Clara María; Taborda-F., Elizabeth (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Tooth agenesis is the most common anomaly of craniofacial development. The purpose of this report is to present a brief review of literature about tooth agenesis, which includes: terminology, etiology, prevalence, associated syndromes and dental anomalies. Two clinical cases are presented. In Colombia there are no studies which allow us to determine the genetic causes of this anomaly, more research is needed in this area in order to clarify its etiology.